PENERAPAN METODE KARYA WISATA PADA BIDANG STUDI IPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SDN 27 KECAMATAN KOTO XI TARUSAN - Beslita Beslita (JRTI (Jurnal Riset Tindakan Indonesia), 2016)
Social Science (IPS) is one of subjects requiring the proof of correlation between theory and real life. Subject of research are students grade VI SDN 27 Kecamatan Koto XI Tarusan. This research was aimed to improve students’ learning achievement for IPS subject after implementation of touring method. Touring method was held out of school by giving grouply assignment. Results of the assignment were shown by each group in the classroom. This reseaarch was held in two cycles. Data of research were obtained from observation sheet, quisionaire, and test. Researcher decided the standard of students’ learning achievement as 60. After cycle I, only 45% of students could reach the standard. Meanwhile, after cycle II, there was 88% of students reaching the standard. Based on the result of research, it can be concluded that implementation of touring method can improve learning achievement of students grade VI SDN 27 Kecamatan Koto XI Tarusan.